Implementasi Kegiatan Pemberdayaan melalui Organisasi Kepemudaan AIESEC in Indonesia - Rahmad Eko Wiranto; Shannaz Mutiara Deniar; Najamuddin Khairur Rijal (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2022)
This research intends to examine how the form and implementation of empowerment activities are carried out by youth organizations through AIESEC in Indonesia. Youth in Indonesia have the potential to actively carry out sustainable development through activities that follow the current situation, making the role of AIESEC provide genuine action to youth by contributing to global empowerment activities. The research method uses qualitative research through library research from several journals, data from AIESEC in Indonesia, and the interview process in this study. The result shows that AIESEC can facilitate empowerment activities with a focus on SDGs through Local Project. A total of 357 participants from 26 universities were able to carry out these activities. The activities carried out by AIESEC has demonstrated that they could have a positive impact to development of youth who participate in the program and have the opportunity to support change. However, the evaluation to look at the implementation is more thoroughly based on the findings of the empowerment activities carried out by AIESEC, especially in Indonesia.